RESPONSE GREEN BEANS TO SPRAY SOME MICRONUTRIENTS AND ADITION ORGANIC FERTILIZER - & Al-JUMAIL, Al-DULAIMI (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment carried out at the research station of the College of Agriculture-University of Baghdad during seasons, spring and autumn 2015. Used in agriculture seeds of hybrid primal, one of the short Cultivars. the aim of the experiment study the effect of iron, zinc spray and add organic nutrient in the vegetative growth and plant yield of green beans. The experiment was designed as an experiment factorial 3 * 4 and three blocks according to the experimental design RCBD includes every block 12 treatments resulting from interaction spray four treatments (0, 0.5 Zn ml. L-1water, 2g Fe.L-1 water and Fe + Zn) and add three levels of humic acid (0, 2 and 3) kg ha-1, after melted in a calculated amount of water and insert into the slot  around the plants per experimental unit.  The results showed the superiority of the treatment of M4 (Fe + Zn) and also the treatment of H2 (3kg  ha Humic) in the studied traits As for coefficients interaction has excelled M4H2 by giving altitude plant higher amounted 59.56 and 53.57cm, the number of branches 5.18 and 4.45 branch. Plant-1, leaf area 67.07 and 54.88dm2 plant-1, the concentration of chlorophyll in the leaves were 238 and 248mg. 100g-1 fresh weight, dry weight of vegetative growth were 63.73 and 54.48g. plant-1, the percentage of flour set were 62.00 and 66.67%, one Plant yield 176.70 and 133.99g.Plant-1 for two seasons, spring and autumn every traits sequentially.